2018
DOI: 10.1016/j.pharmthera.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of depression, ketamine and rapid-acting antidepressants: Is it glutamate inhibition or activation?

Abstract: The discovery of the antidepressant effects of ketamine has opened a breakthrough opportunity to develop a truly novel class of safe, effective, and rapid-acting antidepressants (RAADs). In addition, the rapid and robust biological and behavioral effects of ketamine offered a unique opportunity to utilize the drug as a tool to thoroughly investigate the neurobiology of stress and depression in animals, and to develop sensitive and reproducible biomarkers in humans. The ketamine literature over the past two dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(144 citation statements)
references
References 174 publications
(206 reference statements)
3
122
0
2
Order By: Relevance
“…Briefly, one possibility suggested by this study is that ketamine treats depression without resolving underlying processes, such as neuroinflammation, that produce synaptic elimination and undermine antidepressant effects of ketamine. This hypothesis presumes that the expression of the antidepressant effects of ketamine depends upon sustaining the newly made synapses (6). The anti-inflammatory effects of rapamycin may protect these synapses and thereby extend the antidepressant effects of ketamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, one possibility suggested by this study is that ketamine treats depression without resolving underlying processes, such as neuroinflammation, that produce synaptic elimination and undermine antidepressant effects of ketamine. This hypothesis presumes that the expression of the antidepressant effects of ketamine depends upon sustaining the newly made synapses (6). The anti-inflammatory effects of rapamycin may protect these synapses and thereby extend the antidepressant effects of ketamine.…”
Section: Discussionmentioning
confidence: 99%
“…The antidepressant effects may emerge within hours of a single dose, but without additional ketamine doses, relapse typically occurs in 3-14 days (3)(4)(5). Ketamine and its metabolites are believed to exert antidepressant effects primarily by inducing a prefrontal glutamate neurotransmission surge leading to activation of synaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid glutamate receptors (AMPAR), which increases brain-derived neurotrophic factor (BDNF) levels, enhances stimulation of TrkB receptors, activates the mechanistic target of rapamycin complex 1 (mTORC1), and produces synaptogenesis (6)(7)(8)(9). Several preclinical studies have shown that ketamine administration increases mTORC1 signaling (10)(11)(12)(13), but there are non-replications of this finding (14).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the stress-related prefrontal GBCr deficits were found to normalize following ketamine treatment (17,18,26). Together, these findings have led to the hypothesis that the identified prefrontal GBCr abnormalities may reflect, at least partially, an underlying stress-related synaptic loss and dysconnectivity that have long been reported in preclinical studies of trauma and chronic stress (1,27). Surprisingly, we previously found no prefrontal resting-state GBCr abnormalities in US military veterans suffering from severe PTSD symptoms (28).…”
Section: Introductionmentioning
confidence: 92%
“…Overall, the study findings support our a priori hypothesis of state-dependent symptom-induced increases in cortical GBCr, putatively concealing any GBCr deficits related to synaptic loss. Reduced prefrontal GBCr has been directly associated with trauma-and stress-related synaptic loss (1,27). Moreover, these cortical GBCr deficits have been reported in several psychiatric disorders with a considerable chronic stress component, including unipolar and bipolar depression, obsessivecompulsive disorder, and schizophrenia (17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Figure 3 Overall Salience Global Connectivity In Us Army Somentioning
confidence: 99%
“…In contrast, glutamatergic drugs, such as ketamine, have rapid antidepressant efficacy (11) in treatment resistant, severely depressed patients, sometimes within hours of treatment (12,13). These and other accumulating data indicate glutamatergic abnormalities (14)(15)(16) and differences between the sexes in depression.…”
Section: Introductionmentioning
confidence: 99%